PERANAN MODEL TWO STAY TWO STRAY MATERI IPA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV SEKOLAH DASAR - Alma Dwi Novitasari; Adinda Nur Istirohmah; Aulia Nur Faizah (Jurnal Muassis Pendidikan Dasar, 2023)
This research is based on the problem of learning science in elementary schools which is still not active. Due to learning that only uses the lecture method so as to make students less enthusiastic. so that the teacher prepares learning methods such as using the Two Stay Two Stray (TS-TS) learning model. This study aims to find out how the role of the two stay two stray learning model has on the learning outcomes of students in grade 3 elementary schools. Where in science learning in elementary schools students still cannot achieve maximum results or not (KKM) in science content. So the teacher needs to prepare a strategy before teaching so that students can receive science learning and can be more active. The research method chosen in this study was to use literature or literature studies by collecting several references from libraries, books or journals. The conclusion of the results of this study shows that the Two Stay Two Stray learning model can assist teachers in explaining Science material for Class IV Elementary Schools, helping students to be more active in participating in Science learning activities and the Two Stay Two Stray learning model has a role that can be used to embed science material.